Front elevation of the Chaunsath Yogini Temple - Temples of India Project Team (Jio Institute, 2024)
A view from the west-facing elevation of the Chaunsatha Yogini Temple at Arthuna. Seen here are the plinth of the temple and the partially surviving mulaprasada. The entire mandapa of the temple has fallen.